‘Becoming and being online EFL teachers’: Teachers' professional identity in online pedagogy - Mark B. Ulla; William F. Perales; Veronico N. Tarrayo (Heliyon, 2024)
Teaching online may require teachers to shift to and display a professional identity different from the ones they held in face-to-face classroom teaching. Drawing upon the concept of teacher professional identity (TPI) and employing narrative inquiry as a method, the present study examines how two English as a foreign language (EFL) teachers display their professional identity through reflexivity as they shift experiences of being and becoming online teachers. It also explored how such identity is developed among EFL teachers in Thailand throughout their online teaching experience. The findings underscored how the EFL teachers viewed themselves through reflexivity as beginners as they negotiated their TPI during the sudden transition to online teaching because of the COVID-19 pandemic. Based on the findings, we argue that because TPI is dynamic, the sudden shift to online teaching prompted the teacher-participants to reflect on their experiences and redevelop a professional identity corresponding to online teaching as a new environment. The findings contribute to the literature by highlighting the importance of teachers' reflexivity toward TPI development in online teaching and pedagogy.